If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying H + 12 + -1h = 28 Reorder the terms: 12 + H + -1h = 28 Solving 12 + H + -1h = 28 Solving for variable 'H'. Move all terms containing H to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + H + -12 + -1h = 28 + -12 Reorder the terms: 12 + -12 + H + -1h = 28 + -12 Combine like terms: 12 + -12 = 0 0 + H + -1h = 28 + -12 H + -1h = 28 + -12 Combine like terms: 28 + -12 = 16 H + -1h = 16 Add 'h' to each side of the equation. H + -1h + h = 16 + h Combine like terms: -1h + h = 0 H + 0 = 16 + h H = 16 + h Simplifying H = 16 + h
| 7+-3(5t+-10)=67 | | -90=-12-2.6x | | 17x+18y+19+20x-12y-9= | | 10x-12x-7y=8 | | 7*k=168 | | z^6/z^9 | | 2(v-1)=4v+4-2(-8v-2) | | 75-9h=20+10h | | 3/4(24-8b)2(5b+1) | | 18=4y+(-42) | | -1(9-7c)= | | 5x+17=10-2x | | 9z-3=6z+15 | | 5-8=x | | 12x-33= | | 35+6r=4(-8+4R)+7 | | 5x-(2x+4)=3(3+x) | | -1(20+d)= | | 0.4x(-.03)= | | -20y=100 | | -15+X+6-10=-5 | | 3x^2-4x=2x^2+4x-6 | | -3x-5=2x+7 | | 2(-5+4x)=86 | | W=p+2l | | [3y+1]-1=[y+4] | | 24-5p=17-4p | | 1/2x+y=-2 | | 2/21=-5/7w | | 18x+6= | | X^5+7x^3-18x=0 | | 5z^4+10z^2=54-11z^2 |